Different Word-Meaning In Acehnese - Armia Armia; Iskandar Abdul Samad; Rostina Taib; Subhayni Subhayni; Cut Zuriana; Ramli Ramli; Maya Shafida; Hendra Heriansyah (Proceedings of AICS - Social Sciences, 2021)
Differentiation in word-meaning reflects the diverse variety/type of meaningdeterminationinformation in a language. This occurs in Acehnese which has differenttypes of word-meanings compared to other languages across the globe. A semanticapproach is applied in Acehnese. This research applies a qualitative approach whichdescribes about various meanings of the Acehnese language objectively andcomprehensively. This research found that the words in Acehnese has a varietyof distinctive meanings and tends to be different from other languages, these are (1)denotative meaning, (2) connotative meaning, (3) lexical meaning, (4) grammaticalmeaning, (5) contextual meaning, (6) conceptual meaning, (7) propositional meaning,and (8) pragmatic meaning.Keywords: different, words, meaning, Acehnese.